Natural regeneration of degraded mangrove sites in response to hydrological restoration - Echeverría-Ávila, Stephanie; Pérez-Ceballos, Rosela; Zaldívar-Jímenez, Mario; Canales-Delgadillo, Julio; Brito-Pérez, Roberto; Merino-Ibarra, Martín; Vovides, Alejandra (Instituto de Ecología, A.C., 2019)
The mangroves of Laguna de Términos, Campeche have been affected by the loss of hydrological connection due to tropical storms and hurricanes. The objective of this study was to evaluate the natural regeneration in a degraded area, after having implemented actions of restoration through hydrological restoration. Three sampling sites with different times of restoration (1-3 years), and a preserved natural mangrove site as reference, were established. The sampling was carried out in the years 2014 to 2015. Forest structure (density, height), survival, growth rate of seedlings and environmental characteristics were measured. The relationship between the vegetation and environmental characteristics was determined using simple linear regressions and multidimensional scaling analysis. To determine the dispersal of seedlings, a mixed linear model of the seedling density vs distance vs time of restoration was generated. The results showed that distance to natural mangroves affects the seedling density. The phosphates concentration is related to survival, while the ammonia and sulfide concentrationis negatively related to seedling density. The actions of hydrological restoration influenced the settlement and growth seedling of mangrove vegetation, therefore natural areas of mangroves and the water reconnection facilitated propagule dispersal towards the degraded areas, highlighting the importance of the inclusion of natural areas within the restoration projects.